2016
DOI: 10.2196/jmir.5567
|View full text |Cite
|
Sign up to set email alerts
|

Carbohydrate Estimation by a Mobile Phone-Based System Versus Self-Estimations of Individuals With Type 1 Diabetes Mellitus: A Comparative Study

Abstract: BackgroundDiabetes mellitus is spreading throughout the world and diabetic individuals have been shown to often assess their food intake inaccurately; therefore, it is a matter of urgency to develop automated diet assessment tools. The recent availability of mobile phones with enhanced capabilities, together with the advances in computer vision, have permitted the development of image analysis apps for the automated assessment of meals. GoCARB is a mobile phone-based system designed to support individuals with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
68
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(75 citation statements)
references
References 25 publications
1
68
0
2
Order By: Relevance
“…When the GoCARB application was tested in 19 adults with T1DM, the estimation error of the carbohydrate content of each meal using manual estimation was 28±38 g, whereas when using the GoCARB app, the estimation error was reduced to 12±10 g of carbohydrate. The system correctly identified 85% of the food items contained within the meals 57. The participants rated the usability highly, but delays in the transmission of data and reliance on an Internet connection were seen as negative elements of the application 57…”
Section: Ehealth Technologies To Support Diet and Physical Activity Imentioning
confidence: 96%
“…When the GoCARB application was tested in 19 adults with T1DM, the estimation error of the carbohydrate content of each meal using manual estimation was 28±38 g, whereas when using the GoCARB app, the estimation error was reduced to 12±10 g of carbohydrate. The system correctly identified 85% of the food items contained within the meals 57. The participants rated the usability highly, but delays in the transmission of data and reliance on an Internet connection were seen as negative elements of the application 57…”
Section: Ehealth Technologies To Support Diet and Physical Activity Imentioning
confidence: 96%
“…It uses segmentation to calculate portion sizes, and, by using food recognition, the nutrient profile is built up. The system has been tested in a pre-clinical trial showing greater accuracy than the target users [39], and in a clinical trial which showed a positive impact to the selfmanagement of type 1 diabetes [40].…”
Section: Discussionmentioning
confidence: 99%
“…One of the problems with relying on user meal announcements is that the carbohydrate estimation by the user is often inaccurate, both in time and value. An example of this is reported by [9], where the CHO estimation by diabetes patients was off by 28 g on average. In other cases, users will forget to announce the meal entirely.…”
Section: Introductionmentioning
confidence: 90%
“…Other researchers have investigated systems for automatic carbohydrate estimation based on e.g. images [9]. The drawback here is that while the estimate of the carbohydrate content may be more accurate through computer vision, meal announcement by the user is still needed, as he or she will have to remember to take a picture of every meal.…”
Section: Introductionmentioning
confidence: 99%